Low temperature rolling of AZ91 alloy for hydrogen storage. (7th December 2017) - Floriano, R.; Leiva, D.R.; Melo, G.C.; Ishikawa, T.T.; Huot, J.; Kaufman, M.; Figueroa, S.J.A.; Mendoza-Zélis, L.A.; Damonte, L.C.; Botta, W.J.
Abstract: The hydrogen storage properties of a commercial AZ91 magnesium alloy were investigated after processing by cold rolling in two different conditions: (a) extensive cold rolling at room temperature (CR); (b) rolling with the immersion of the alloy in liquid nitrogen bath after 05 rolling passes. This second condition is named as low temperature rolling (LTR). A full microstructural characterization including scanning and transmission electron microscopy (SEM and TEM), X-ray diffraction (XRD), X-ray photoelectron and positron annihilation life time spectroscopy (XPS and PALS) were performed in the processed alloys. The hydrogen storage properties were measured using a Sievert-type apparatus. The AZ91-alloy is composed by the β-Mg and Mg17 Al12 phases, and after processing by CR, an intense peak broadening and strong [002] texture were observed in the alloys. The LTR processing resulted in a more fragile material containing more microcracks and exposed interfaces than the conventionally cold rolled one. The LTR sample also presented a more refined microstructure in comparison with CR sample. These features resulted in superior hydrogen storage properties for the LTR sample in comparison with the CR sample. In addition, the effect of surface contamination was also studied in detail and it was found to play a significant role during the activation kinetics. Highlights: A new processing technique called "Low Temperature Rolling- LTR" has been shown. LTR samples have much better hydrogen sorption/desorption kinetics and capacity than CR samples. A much finer microstructure was observed for the LTR in comparison with the CR samples. The effect of surface contamination under activation kinetics was investigated by XPS and SEM analysis.